RESULTS AND EFFECTIVENESS OF EXPERIMENTAL RESEARCH ON DEVELOPING SPIRITUAL AND MORAL QUALITIES IN YOUNG SCHOOLCHILDREN THROUGH TOURISM - Abdumannatov Elbek Abdumajitovich; Ravshanqulova Dilora Ravshanovna (FAN VA TA’LIM INTEGRATSIYASI (INTEGRATION OF SCIENCE AND EDUCATION), 2024)
This article presents the results of scientific research on the development of spiritual and moral qualities in young schoolchildren through tourism. During the experimental studies, experimental and control groups were formed, each consisting of 47 students. The level of development of students' spiritual and moral qualities was determined through initial and final experimental tests. According to the results, students in the experimental group showed a higher level of development of these qualities.